Sintering temperature-microstructure-property relationships of alumina matrix composites with silicon carbide and silica additives - Limpichaipanit A. (2017)
© 2017 Walter de Gruyter GmbH, Berlin/Boston 2017. Alumina-based composites were fabricated by reaction sintering from two different sintering powder mixtures: Alumina with silica (SiO 2 ) and alumina with silicon carbide (SiC; to allow oxidation to form SiO 2 ). After sintering, SiO 2 underwent complete reaction to form alumina/mullite composites. In terms of microstructure, the density and grain size of ceramic samples were investigated. The density of the composites prepared by alumina and SiC was lower than those of alumina and the composites prepared by alumina and SiO 2 . The grain size increased as the sintering temperature increased. In terms of mechanical properties, fracture surfaces, hardness, and fracture toughness were investigated. It was found that the fracture surface of alumina was rather intergranular, whereas the fracture surface of the composites was more transgranular. The hardness of the composites was higher than that of alumina at the same sintering temperature. However, the fracture toughness of the composites was not significantly different compared to that of alumina.